Catalytic Phenol Hydroxylation with Dioxygen: Extension of the Tyrosinase Mechanism beyond the Protein Matrix1. Issue 20 (22nd April 2013) - Hoffmann, Alexander; Citek, Cooper; Binder, Stephan; Goos, Arne; Rübhausen, Michael; Troeppner, Oliver; Ivanović‐Burmazović, Ivana; Wasinger, Erik C.; Stack, T. Daniel P.; Herres‐Pawlis, Sonja
<x xml:space="preserve">Abstract</x> A new catalyst (see structure) hydroxylates phenols with O2 via a stable side‐on peroxide complex, which is similar to the active site of tyrosinase in terms of the ligand environment and its spectroscopic properties. The catalytic oxidation of phenols to quinones proceeds at room temperature in the presence of NEt3 and even non‐native substrates can be oxidized catalytically. The reaction mechanism is analogous to that of the enzyme‐catalyzed reaction.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>